Analisis Semiotik Resistensi Ketimpangan Relasi Gender pada Film Perempuan dari Pulau Rote - Sheron Mariana Alezandra Engelbert; Merry Fridha Tripalupi; Teguh Priyo Sadono (Universitas Merdeka Malang, 2026)
This study analyzes the representation of patriarchy and women’s resistance in the film Women from Rote Island using Roland Barthes’ semiotic framework. Through a qualitative approach and repeated viewing of the film, data were examined across three levels of meaning. At the denotative level, the film shows scenes of violence, control, and social inequality affecting women. At the connotative level, these images reveal stigma, subordination, and the emergence of symbolic resistance through courage and solidarity. At the myth level, patriarchy appears as a naturalized ideology, while the film constructs a counter-myth that repositions women as independent agents capable of challenging injustice. The study concludes that tradition is negotiable and the film functions as a cultural critique of gender relations in traditional societies.